Investigating the fire resistance of corrugated steel columns - Qusay Al-Kaseasbeh (Results in Engineering, 2024)
This research paper focuses on investigating the fire resistance of axially restrained Corrugated Plate Steel columns (CRG) exposed to hydrocarbon fire conditions. Key parameters, including corrugation depth, plate thickness, axial load percentage, and column length, were analyzed to assess their impact on the fire resistance performance of CRG columns. A comprehensive analysis involving 80 finite element (FE) models was conducted using ABAQUS software. The analysis process encompassed studying temperature distribution within the columns, observing buckling modes, and determining the durations of buckling and failure fire resistance. The adopted FE model has been verified by comparing it to experimental data presented in the relevant literature. Findings reveal that corrugated CRG columns exhibit superior resistance to buckling and structural failure compared to circular cross-section columns. Corrugation depth minimally affects fire resistance but influences axial deformation and generated axial force due to increased structural stiffness. Increasing plate thickness improves fire resistance, particularly at lower axial load levels, while increasing axial load percentage decreases fire resistance. Doubling the column length has no significant effect on fire resistance, but columns with smaller plate thicknesses exhibit lower resistance under high axial load conditions. These insights inform the design and construction of CRG columns in structures exposed to hydrocarbon fire risks, aiding in enhancing fire safety and performance.